Discoid lupus erythematosus with epithelial dysplasia: a case report - Rai, Harishchandra; Dayakar, Anitha; H., Supriya; Sojan, Elizabeth (International Journal of Research in Medical Sciences, 2017)
Lupus erythematosus is a classic example of an immunologically mediated condition and is one of the most common of the so called “collagen vascular” or connective tissue diseases. Lupus erythematosus was first described by Biett in 1828 and Kaposi in 1872. Development of squamous cell carcinoma (SCC) can occur in DLE, with about 20 cases reported in the world literature to-date, which led the World Health Organization (WHO) to classify DLE as one of the precancerous conditions. Thus malignant changes in such a condition must be given utmost importance. This article focuses on a rare case of DLE with epithelial dysplasia.